ANALYSIS OF THE JUDGE'S DECISION ON THE LEGAL CONSEQUENCES OF LAND SALES AND PURCHASES UNDER THE HAND (CASE STUDY: DECISION NO. 107/PDT.G/2021/PN SRP - Endah Wulandari (RADJA PUBLIKA, 2026)
Abstract : Land sales and purchases are explained in Article 37 paragraph 1 of Government Regulation No. 24 of 1997 which states that land sales and purchases carried out underhand can be registered if they can be proven with a deed issued by a Land Deed Official (PPAT) or other authorized officials based on applicable laws. Land sales and purchases underhand have been carried out by people in Indonesia because of the ease of the process and the low costs incurred. However, underhand sales and purchases can cause various land problems because there is no sale and purchase deed issued by the PPAT as one of the requirements for registering the transfer of rights. With these conditions, this article aims to examine the legal consequences of underhand land sales and purchases by taking the example of the case : Decision No. 107/Pdt.G/2021/PN Srp using a qualitative method with a case study approach. The results of this study indicate that there are four provisions for the validity of sales and purchases according to the Civil Code. In this case, the underhand land sale and purchase in Decision No. 107/Pdt.G/2021/PN Srp is valid under customary law and according to UUPA, but is not valid according to the Civil Code because it does not meet the requirements for validity, namely 'certain matters', namely that the Plaintiff is unable to pay within the time period written in the sales and purchase agreement.